Fast Broadband Scattering Computation for Finite Periodic Arrays using the Characteristic Basis Function Method and the Best Uniform Rational Approximation - Li, Fang; Zhang, Hai Rong; Chen, Lin; Wang, Xing (Applied Computational Electromagnetics Society Journal (ACES), 2024)
In this paper, a hybrid method combining the characteristic basis function method (CBFM) and the best uniform rational approximation (BURA) technique for fast wideband radar cross-section (RCS) prediction of finite periodic arrays is proposed. The traditional CBFM requires reconstructing the reduced matrix at each frequency point, which is very time-consuming when calculating the wideband RCS of the target. By introducing the BURA technique, the hybrid method is proposed to efficiently calculate the wideband RCS. The target is first divided into several easily solvable subdomains. Then, the surface integral equation is solved by the characteristic function method to obtain the equivalent surface current at the Chebyshev node. Afterwards, the surface current in a desired frequency band is represented by the Chebyshev series. To improve accuracy, the Chebyshev series is matched with the Maehly approximation. After obtaining the current coefficients in the whole bandwidth, the current density at any frequency point in the bandwidth can be calculated. Finally, the broadband electromagnetic scattering characteristics of the finite periodic arrays can be obtained.